Being and Creation in the Theology of John Scottus Eriugena : an Approach to a New Way of Thinking. - Sushkov, Sergei N.; Jasper, David (Eugene : Wipf and Stock Publishers, 2017)
Despite his prominent role in the formation of Christian thought, John Scottus Eriugena still remains an enigmatic figure whose background and potential arouse a great deal of scholarly interest. This is true especially today, when faith seeks to regenerate: his honesty and profundity encourage us in our search for the authentic teaching of Christ. As a theologian who strongly believes in human dignity as equal to that of the imago dei, Eriugena helps us meet Christ again and follow him towards a new horizon of being. What makes Eriugena's theology unique is his innovative approach to theologi.
Pages:1 to 25; Pages:26 to 50; Pages:51 to 75; Pages:76 to 100; Pages:101 to 125; Pages:126 to 150; Pages:151 to 175; Pages:176 to 200; Pages:201 to 225; Pages:226 to 230.
Print version record.
Includes bibliographical references
eBooks on EBSCOhost
Keywords: Erigena, Johannes Scotus, -- approximately 810-approximately 877.; Erigena, Johannes Scotus, -- approximately 810-approximately 877; Philosophy of nature; Philosophie de la nature; SCIENCE -- Cosmology; Philosophy of nature; Electronic books